2021
DOI: 10.1109/tit.2020.3022515
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of Quantum Private Information Retrieval With Multiple Servers

Abstract: We study the capacity of quantum private information retrieval (QPIR) with multiple servers. In the QPIR problem with multiple servers, a user retrieves a classical file by downloading quantum systems from multiple servers each of which contains the copy of a classical file set while the identity of the downloaded file is not leaked to each server. The QPIR capacity is defined as the maximum rate of the file size over the whole dimension of the downloaded quantum systems. When the servers are assumed to share … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 45 publications
2
22
1
Order By: Relevance
“…The relaxation made to the SPIR definition would allow us to use another protocol used as the foundation for Song et al's quantum SPIR protocol [26]. In this protocol, we label the user's desired bit as w i (n) = n…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relaxation made to the SPIR definition would allow us to use another protocol used as the foundation for Song et al's quantum SPIR protocol [26]. In this protocol, we label the user's desired bit as w i (n) = n…”
Section: Discussionmentioning
confidence: 99%
“…Kerenidis et al focuses on how SPIR can be performed without shared randomness if the user is honest [25]. Song et al proposed a quantum multi-database SPIR, but requires shared entanglement between the data centres and assumes secure classical and quantum channels [26].…”
Section: Introductionmentioning
confidence: 99%
“…When two-way quantum communication is allowed, Le Gall [23] proposed a one-server QPIR protocol whose communication complexity is the square root of the size of all files. Song and Hayashi [27], [28] discussed the QPIR capacity, which is the maximum ratio of the file size to the size of the downloaded quantum systems when the upload from the user to the servers is classical, the download is quantum, and the servers share entanglement before the protocol starts. They showed that the QPIR capacity is 1 and proposed a capacity-achieving QPIR protocol with only two servers.…”
Section: A Classical and Quantum Private Information Retrievalmentioning
confidence: 99%
“…In the quantum case, the paper [21] proved that symmetric QPIR can be implemented if two-way quantum communication is available. The paper [27] showed that symmetric QPIR is also possible with the classical upload, quantum download, and shared entanglement, and derived that the symmetric QPIR capacity is 1.…”
Section: A Classical and Quantum Private Information Retrievalmentioning
confidence: 99%
See 1 more Smart Citation